Determinant of Households Consumption Behavior in UAE: A Comparison of Nationals and Expatriates - Katsaiti, Marina-Selini; Ahmad, Khalifa Abdulrahman Abdulla; Tajuddin, Hamid Mohammadi; Abdulrouf, Shahabuddin (European Scientific Journal, ESJ, 2017)
The United Arab Emirates during the past 45 years has achieved startling economic growth rates; therefore, it is crucial to examine the consumption pattern in the UAE. This study aims to introduce the pattern of the household consumption behavior to the literature. The outcome of this study can provide useful information to policy makers by allowing them to gain important insights on household’s consumption needs and expenditure allocation. This study used survey data collected from interviewing random household participants in malls in Dubai, Abu Dhabi, and Alain. On March 2015 a sample of 254 were examined, of men and women, and expatriates and nationals. We investigate consumption habits of the type of goods and services people buy, normal against luxuries. Then, we use empirical estimations to examine the determinants of household expenditures. In our study, we find that in general nationals spend more than expatriates do; for the whole sample, most expenditure is concentrated on food, education, and housing. Our results show that household structure does not affect the consumption behavior of a national household as it does to the expatriates. In addition, younger people consume more than the older ones, while married consume more than the rest.